2014
DOI: 10.1007/s10103-014-1677-2
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and ultrastructural modifications of postmenopausal atrophic vaginal mucosa after fractional carbon dioxide laser treatment

Abstract: Vaginal atrophy occurring during menopause is closely related to the dramatic decrease in ovarian estrogens due to the loss of follicular activity. Particularly, significant changes occur in the structure of the vaginal mucosa, with consequent impairment of many physiological functions. In this study, carried out on bioptic vaginal mucosa samples from postmenopausal, nonestrogenized women, we present microscopic and ultrastructural modifications of vaginal mucosa following fractional carbon dioxide (CO2) laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
155
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(190 citation statements)
references
References 20 publications
14
155
0
11
Order By: Relevance
“…Complications were rare with slight clinical significance: three women experienced post-coital urinary tract infections, two reported vaginal discharge, three women experienced lower pelvic pain, one had genital herpes and finally two women presented postmenopausal bleeding (benign in endometrial biopsies). The described clinical observations were confirmed by Zerbinati et al [57] in a histological evaluation of the vaginal biopsies using light and electron microscopy. The study was conducted on a group of 50 post-menopausal women presenting GSM symptoms with CO 2 laser -SmartXide 2 V 2 LR.…”
Section: Fractional Co 2 Laser In the Treatment Of Vvasupporting
confidence: 61%
“…Complications were rare with slight clinical significance: three women experienced post-coital urinary tract infections, two reported vaginal discharge, three women experienced lower pelvic pain, one had genital herpes and finally two women presented postmenopausal bleeding (benign in endometrial biopsies). The described clinical observations were confirmed by Zerbinati et al [57] in a histological evaluation of the vaginal biopsies using light and electron microscopy. The study was conducted on a group of 50 post-menopausal women presenting GSM symptoms with CO 2 laser -SmartXide 2 V 2 LR.…”
Section: Fractional Co 2 Laser In the Treatment Of Vvasupporting
confidence: 61%
“…In an independent study by Zerbinati et al (2015) on biopsies from vaginal mucosa samples extracted from 50 postmenopausal, nonestrogenized women treated with the MonaLisa, restoration of the vaginal thick squamous stratified epithelium with a significant storage of glycogen in the epithelial cells was observed together with fibroblast activation and neosynthesis of extracellular matrix. The laser settings used in this study were energy fluence above 100 mJ per pulse, with a pulse duration of 1,000 μs, and a single spot size of 200 μm.…”
Section: Laser-based Devices For Vaginal Rejuvenationmentioning
confidence: 98%
“…Decreasing levels of estrogen cause thinning and atrophy, loss of elasticity, and loss of functionality of the vaginal mucosa, leading to dryness, itching, burning, dysuria, and dyspareunia. [34][35][36] AFLs can play a role in stimulating the tissue to restore structure and function. In a large study of 386 patients, 3 treatments with a fractional microablative CO2 laser showed a resolution of the aforementioned symptoms in a majority of patients.…”
Section: Skin Rejuvenation and Skin Tighteningmentioning
confidence: 99%
“…Histological studies have confirmed a successful remodeling of the vaginal mucosa, with a thickened epithelium with increased glycogen content, as well as increased collagen in the lamina propria. 35 Vaginal laser treatments are tolerated with minimal pain, while vulvar treatments can be more uncomfortable.…”
Section: Skin Rejuvenation and Skin Tighteningmentioning
confidence: 99%